Effect of using Nylon Fibers in Self Compacting Concrete (SCC) - Mujahid Hussain Lashari; Noor Ahmed Memon; Muneeb Ayoub Memon (Civil Engineering Journal, 2021)
The self-compacted concrete (SCC) is a special type of concrete which settles down in the formwork and fills its every corner without any use of compaction or vibration. As SCC has higher flow-ability that causes brittle behaviour resulting in poor performance under tension and bending. The inclusion of randomly distributed short and discrete fibers is one of the most effective way to improve the tensile as well as flexural performance of SCC. In this regard this experimental study is undertaken to investigate the effect of nylon fibers (NF) on fresh and hardened properties of SCC. Two different lengths; 20 mm and 12 mm and five different volumetric percentages; 0.1, 0.2, 0.3, 0.4 and 0.5% of NF were used. The results revealed that addition of NF slightly affects the fresh properties of SCC. However, the extent of the effect is not of that order to be considered as major factor. The fresh properties for entire mixes lie within the required range according to EFNARC guidelines. The strength properties increases with addition of NF, the extent of increment is greater for the longer length of NF. The optimum volumetric fraction of NF for producing high strength SCC was found as 0.5%. Doi: 10.28991/cej-2021-03091734 Full Text: PDF